RESEARCH OF THE CHEMICAL AND MINERALOGICAL PROPERTIES OF THE LIMESTONE OF THE ZHAMANSAI DEPOSIT OF THE REPUBLIC OF KARAKALPAKSTAN - AS A RAW MATERIAL FOR THE PRODUCTION OF PORTLAND CEMENT CLINKER - Zhaksilikovna, Orazymbetova Gulistan (International Journal of Psychosocial Rehabilitation, 2020)
— This paper makes analyses of the research of the chemical and mineralogical properties of the limestone of the Zhamansai deposit of the Republic of Karakalpakstan. On this case, as a raw material for the production of portland cement clinker was analysed in the research area of the region. Finally, research has done analyses on the various points while showing both outcomes and shortcomings as the whole.